Biocompatibility of hydrogel derived from equine tendon extracellular matrix in horses subcutaneous tissue - De Castilho, Thiago; Rosa, Gustavo dos Santos; Stievani, Fernanda de Castro; Apolônio, Emanuel Vítor Pereira; Pfeifer, João Pedro Hübbe; Altheman, Vittoria Guerra; Palialogo, Valéria; Santos, Nilton José Dos; Fonseca-Alves, Carlos Eduardo; Alves, Ana Liz Garcia (Frontiers in Bioengineering and Biotechnology, 2024)
Tendinopathies account for a substantial proportion of musculoskeletal injuries. To improve treatment outcomes for partial and total tendon ruptures, new therapies are under investigation. These include the application of mesenchymal stem cells (MSCs) and biocompatible scaffolds derived from the Extracellular Matrix (ECM). Synthetic polymer hydrogels have not demonstrated results as promising as those achieved with ECM hydrogels sourced from the original tissue. This study aimed to evaluate the biocompatibility of a hydrogel formulated from equine tendon ECM. Six horses were administered three subcutaneous doses of the hydrogel, with a saline solution serving as a control. Biopsies were conducted on days 7, 14, and 56 post-application to gauge the hydrogel's impact. Throughout the experiment, the horse's physical condition remained stable. Thermographic analyses revealed a temperature increase in the treated groups compared to the control group within the initial 12 hours. The von Frey test, used to measure the mechanical nociceptive threshold, also showed significant differences between the treated group and the control group at 6 hours, 21 days, and 28 days. Histopathological analyses identified an inflammatory response on day 7, which was absent on days 14 and 56. Transmission electron microscopy indicated a decrease in inflammatory cellularity, while immunohistochemistry staining suggested an increased presence of inflammatory factors on day 14. In summary, the hydrogel is easily injectable, triggers a temporary local inflammatory response, and integrates into the adjacent tissue from day 14 onwards.